Improving the Ability of Principals to Carrying Out Academic Supervision Through Managerial Supervision with a Collaborative Approach - Imam Sujianto; Dwikoranto Dwikoranto; Marsini Marsini (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The purpose of this school action research is to improve the ability of school principals to carry out academic supervision through managerial supervision with a collaborative approach. This research was conducted at Foster Vocational Schools in Bojonegoro Regency. The school is a school fostered by researchers who serve as supervisors. The subjects in this study were six principals of vocational school Taruna Mandiri Ngasem, vocational school Association of Teachers of the Republic of Indonesia 3 Bojonegoro, vocational school Al Kyai Sukosewu, vocational school Wali Songo Sugihawaras, vocational school Muhammadiyah 6 Kedungadem, and vocational school Miftahul Huda Baureno. This research was carried out for two months. Method: A collaborative approach with monitoring and evaluation, and workshops is an activation process that will be aimed at finding out whether the development of the implementation of this program, whether it is by plans, procedures, or standards that have been set and assess the level of achievement and effectiveness of the program that has been implemented. Results: the managerial supervision of the collaborative approach can improve principals' performance abilities in carrying out academic supervision. The results achieved in cycle 1 averaged 75.38, and cycle 2 achieved an average score of 92.42 according to the researcher's target, namely the average score of 80 and above. With the increased performance of school principals in academic supervision, all supervised teachers experience direct positive benefits from academic supervision. Novelty: Teachers feel that implementing learning in schools becomes more qualified, effective, and efficient.